Inflammatory Indices and MAFLD Prevalence in Hypertensive Patients: A Large-Scale Cross-Sectional Analysis from China - Shen D; Cai X; Hu J; Song S; Zhu Q; Ma H; Zhang Y; Ma R; Zhou P; Yang W; Hong J; Zhang D; et al. (Journal of Inflammation Research)
Di Shen,1,* Xintian Cai,2,* Junli Hu,2 Shuaiwei Song,1 Qing Zhu,2 Huimin Ma,2 Yingying Zhang,2 Rui Ma,2 Pan Zhou,2 Wenbo Yang,2 Jing Hong,2 Delian Zhang,2 Nanfang Li2 1Graduate School, Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China; 2Hypertension Center of People’s Hospital of Xinjiang Uygur Autonomous Region, Xinjiang Hypertension Institute, NHC Key Laboratory of Hypertension Clinical Research, Key Laboratory of Xinjiang Uygur Autonomous Region, Hypertension Research Laboratory, Xinjiang Clinical Medical Research Center for Hypertension (Cardio-Cerebrovascular) Diseases, Urumqi, Xinjiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Nanfang Li, Hypertension Center of People’s Hospital of Xinjiang Uygur Autonomous Region, Xinjiang Hypertension Institute, NHC Key Laboratory of Hypertension Clinical Research, Key Laboratory of Xinjiang Uygur Autonomous Region “Hypertension Research Laboratory”, Xinjiang Clinical Medical Research Center for Hypertension (Cardio-Cerebrovascular) Diseases, No. 91 Tianchi Road, Urumuqi, Xinjiang, 830001, People’s Republic of China, Tel +86 8564818, Email lnanfang2016@sina.comObjective: Hypertension development and progression are largely influenced by inflammation, which plays a critical role by activating the immune system and causing damage to the vascular endothelium. Metabolic dysfunction-associated fatty liver disease (MAFLD) is also associated with chronic low-grade inflammation, which drives disease progression via metabolic imbalances and adipose tissue dysfunction. This study investigates the relationship between inflammatory indices and MAFLD in hypertensive patients and assesses the predictive accuracy of these indices for MAFLD.Methods: We performed a cross-sectional analysis involving 34,303 hypertensive patients from a Chinese hospital-based registry. The diagnosis of MAFLD was established using metabolic dysfunction criteria alongside evidence of hepatic steatosis confirmed through imaging. Complete blood counts were used to calculate inflammatory indices, including the monocyte-to-lymphocyte ratio (MLR), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic inflammatory response index (SIRI), systemic immune-inflammation index (SII), and aggregate index of systemic inflammation (AISI). To assess the relationship between inflammatory indices and MAFLD, multivariable logistic regression was performed with adjustments for potential confounders. The diagnostic performance of these indices was analyzed using receiver operating characteristic (ROC) curves and area under the curve (AUC) calculations.Results: Patients with MAFLD exhibited significantly elevated levels of all inflammatory indices compared to those without. After multivariable adjustment, each standard deviation increase in AISI, SIRI, and SII was associated with a 74%, 62%, and 58% increased odds of MAFLD, respectively. The AUC for AISI was 0.659, indicating moderate diagnostic accuracy. The AUCs for SIRI and SII were 0.626 and 0.619, respectively, while NLR, PLR, and MLR had lower AUCs of 0.593, 0.558, and 0.589, respectively.Conclusion: In hypertensive patients, inflammatory indices, especially AISI, show a strong association with MAFLD, indicating their potential utility in risk stratification within clinical settings. Further research is needed to evaluate the effectiveness of these markers in the management of MAFLD. Keywords: metabolic-dysfunction-associated fatty liver disease, inflammatory indices, hypertension, diagnostic accuracy